2017
DOI: 10.2147/jpr.s154815
|View full text |Cite
|
Sign up to set email alerts
|

Does transcutaneous electrical nerve stimulation reduce pain and improve quality of life in patients with idiopathic chronic orchialgia? A randomized controlled trial

Abstract: BackgroundChronic orchialgia is defined as testicular pain, which may be either unilateral or bilateral, lasting for more than 3 months. It disturbs a patient’s daily activities and quality of life (QoL), inciting the patient to search for treatments to alleviate the pain. It is estimated that 25% of chronic orchialgia cases are idiopathic.PurposeThe purpose of this study was to investigate how effective transcutaneous electrical nerve stimulation (TENS) is in pain reduction and how it consequently affects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
5
0
7
Order By: Relevance
“…Electrotherapy is a non-pharmaceutical and non-invasive method for pain reduction, which includes transcutaneous electrical stimulation (TENS), laser photobiomodulation, ultrasound, magnetic therapy and interferential current [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Electrotherapy is a non-pharmaceutical and non-invasive method for pain reduction, which includes transcutaneous electrical stimulation (TENS), laser photobiomodulation, ultrasound, magnetic therapy and interferential current [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 34 studies were included in this systemic review; six prospective, 21 retrospective and seven case series. Most studies reported the results of microsurgical spermatic cord denervation (MSCD) (n = 19) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], while the remaining studies investigated the impact of various nerve-blocking techniques (n = 8) [28][29][30][31][32][33][34][35], vasectomy reversal (n = 5) [36][37][38][39][40], and extirpative surgery (n = 2) [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of TENS are mediated through a number of receptors in the CNS and PNS including opioid, serotonin, muscarinic and α 2adrenergic receptors [46]. A single randomised clinical trial by Tantawy et al [28] was conducted on 71 patients with CO who were randomised into a study group (analgesia + TENS, n = 36) and a control group (analgesia alone, n = 35). The TENS was performed five-times per week for 4 weeks, where the anode electrode was placed in the suprapubic area medial to the iliofemoral ligament and the cathode 5 cm proximal to it.…”
Section: Transcutaneous Electrical Nerve Stimulation (Tens)mentioning
confidence: 99%
“…3,6,[25][26][27] However, chronic pelvic pain in men has not been as sufficiently studied as chronic pelvic pain in women. 3,4 In a randomized controlled trial, Tantawy et al 28 investigated how effective transcutaneous electrical nerve stimulation (TENS) is in pain reduction and how it consequently affects the quality of life in patients with ICO. The results demonstrated that TENS is effective in reducing pain and improving quality of life in cases of ICO.…”
Section: Discussionmentioning
confidence: 99%